Stratifying the NHS diabetic eye screening programme: into the unknown? - Sampson, Christopher James; James, Marilyn; Broadbent, Deborah M.; Harding, Simon P. (Wiley, 2016)
In this commentary, we consider the recent recommendation by the UK National Screening Committee (NSC) that people with diabetes at low risk of sight loss should be invited to screening every 2 years rather than annually [1]. We broadly support this recommendation but believe that there are important outstanding questions that require attention before such a policy is implemented. We discuss the decision in the context of the history of the NHS Diabetic Eye Screening Programme (NDESP) and reflect on the current state of evidence, including work cited by the NSC [1–4].